FEATURES OF FUNERAL AND MOURNING RITES IN THE PRE-ISLAMIC PERIOD - Djumanov, Abdulla (Oriental Journal of Education, 2025)
This article analyzes the features of rituals that existed before the adoption of Islam, based on information recorded in written sources, inscriptions and relevant literature, from the point of view of the history of the development of funeral rites, their specificity, theoretical foundations of ideas about death and their description in various spheres. It also presents reflections on the place of funeral rites in public life and the role of burial-related objects in people's everyday life.